Linking Emotional Intelligence and Performance at Work : Current Research Evidence With Individuals and Groups. - Urch Druskat, Vanessa (Taylor and Francis, 2013)
In this edited volume, leading edge researchers discuss the link between Emotional Intelligence (EI) and workplace performance. Contributors from many areas such as social science, management (including organizational practitioners), and psychologists have come together to develop a better understanding of how EI can influence work performance, and whether research supports it. A unique feature of this book is that it integrates the work of social scientists and organizational practitioners. Their mutual interests in EI provide a unique opportunity for basic and applied research and pra.